The anatomy of the arterial supply of the pelvic limb of the porcupine (Histrix cristata) - Yilmaz, S; Karan, M (Veterinary Faculty, 2001)
The aim of this study was to investigate the anatomy of the arterial supply and branches of the pelvic limb of the porcupine. For this purpose, five (three males and two females) adult porcupines were used. The vascular tree of the pelvic limb was injected through the common carotid arteries with coloured latex. The a. iliaca communis arose from the abdominal aorta at the level of the third lumbar vertebra. The only branch arising from a. iliaca externa was a. iliolumbalis. A. profunda femoris was divided into four branches. Tr. pudendoepigastricus appeared in three of the five porcupines examined and gave off a. abdominalis caudalis and a. epigastrica cranialis. A. saphena was divided into a. digitalis communis II - III, III - IV and IV - V on the foot. They gave off aa. digitales plantares propriae. A. poplitea gave off 8 - 10 genicular branches to the knee joint and the muscular branches. The terminal branches of a. tibialis cranialis were a. digitalis dorsalis communis II - III, III - IV and IV - V which gave off aa. digitales dorsales propriae. A. tibialis caudalis gave off medial and caudal branches to the joint at the tarsal joint. It also gave off a branch for the first toe which ran along the medial border of the foot and numerous palmar branches. In conclusion, despite a partial resemblance to the rabbit as a related species, the distribution of the pelvic limb arteries in the porcupine was completely different from other rodents, such as the rat and mouse, and from other mammals. This study is, to our knowledge, the first on the distribution of the pelvic limb arteries in the porcupine.
Keywords: arterial supply; Hystrix cristata; pelvic limb; porcupine